(untitled) (Academia Journal of Medicine, 2021)
Background : Acute poisoning of organophosphorous compound has reached epidemic extent in largely element of the country mainly in developing countries like India. Case reports on clinical implication of total serum creatine phosphokinase in acute OP compound intake has been accounted occasionally, however there are no great extent studies with mention to total serum creatine phosphokinase level in OP compound. Hence this is an attempt to study the total serum creatine phosphokinase in assessing the severity of OP compound poison. Subjects & Methods: Patients with history of OP compound consumption getting admitted in Department of Medicine, Gujarat Adani Institute of medical Science, Bhuj, Kutch, Gujarat during the period of two years were occupied up for study in view of inclusion and exclusion criteria. Information needed for this study collected through a proforma and pre-test proforma from every patient. Results: The levels of CPK were elevated significantly in patients with respiratory failure. In this study 7 out of 8 patients with raised initial CPK level has respiratory failure and eventually death. Only one patient with mildly elevated CPK level has no respiratory failure. Conclusion: In this study only 8 out of 100 case shows raised total serum CPK level. Seven out of 8 positive case who developed respiratory failure and death. All 7 patients has marked raise in total serum CPK level. So the initial raise in total serum CPK level correlated well with severity of OP compound poison and prognosis, suggesting its use as a prognostic indicator of OP compound poison.